Regional convergence in the European Union (1985-1999). A spatial dynamic panel analysis - Gabriele Tondl; Harald Badinger; Werner Müller (European Regional Science Association (ERSA), 2003)
We estimate the speed of income convergence for a sample of 196 European NUTS 2 regions over the period 1985-1999. So far there is no direct estimator available for dynamic panels with strong spatial dependencies. We propose a two-step procedure, which involves first spatial filtering of the variables to remove the spatial correlation, and application of standard GMM estimators for dynamic panels in a second step. Our results show that ignorance of the spatial correlation leads to potentially misleading results. Applying a system GMM estimator on the filtered variables, we obtain a speed of convergence of seven per cent.
Keywords: 330